Plant genomic and microbial interplay in the rhizosphere under salt stress: a review - Ren, Yi; Yan, He; Ma, Aiyuan (Frontiers in Plant Science, 2026)
Soil salinization has been considered as a global problem in agriculture, which decreases crop productivity and threatens food security. Salt stress causes complex physiological damages in plants such as ionic imbalance, osmotic stress, and oxidative damage. However, plants have developed several genomic mechanisms to reduce these negative influences that are further supported by dynamic interactions with rhizosphere microbial communities. This review integrates current advances in understanding the interplay between plant genomes and the rhizosphere microbiome under salt stress. It highlights the role of plant-growth-promoting rhizobacteria (PGPR), arbuscular mycorrhizal fungi (AMF), and microbial volatiles in modulating gene expression and root architecture. Notably, PGPR such as Enterobacter sp. SA187 and Bacillus velezensis have been shown to upregulate key stress-related genes and increase antioxidant enzyme activities, which boost plant resilience under salinity. These microbes also influence stress signaling pathways such as SOS and ABA. Furthermore, this review also discusses the effect of root exudates on microbial communities, the application of synthetic microbial consortia, and genome-scale strategies such as transcriptomics, GWAS, and CRISPR. Our findings show that root exudation patterns shift significantly under salt stress, which enriches beneficial microbial taxa such as Sphingomonas and Streptomyces, while volatile compounds like benzenoids and ketones contribute to systemic stress responses. Understanding the synergistic plant–microbe interactions provides a foundation to engineer salt-resilient crops and for the advancement of sustainable agricultural practices in saline soils.